José María Panganiban’s “La Universidad de Manila” and the Liberal Campaign for Reforms in Philippine Higher Education - Rugeria, Javier Leonardo (Archīum Ateneo, 2021)
Thisarticle examines José María Panganiban’s “La Universidad de Manila” columns in La Solidaridad and discusses their five salient points of criticism of the state of higher education at the Universidad de Santo Tomás in the late nineteenth century. In view of the existing historiography, it argues that Panganiban’s critique of the university, although born out of propaganda, finds empirical grounding in his years of study at Santo Tomás from 1882 to 1888. Lastly, it illustrates that Panganiban’s columns represented a wider, liberal campaign for reforms in Philippine higher education that took place in Madrid and Barcelona from 1888 to 1891.KEYWORDS: JOSÉ MARÍA PANGANIBAN • UNIVERSITY OF SANTO TOMAS • PROPAGANDA MOVEMENT • PHILIPPINE EDUCATION • SECULARIZATION